A new species of Capparidastrum (Capparaceae Juss.) from the Cauca inter Andean valley of Colombia - Mercado-Gómez, Jorge D.; Morales-Puentes, María Eugenia (Phytotaxa, 2020)
We describe and illustrate a new species of Capparidastrum subgen. Pulviniglans (Capparaceae). Capparidastrum dugandii occurs in tropical dry forest fragments of the Colombian inter-Andean valley of the Dagua River, near the municipality of Santa Fe de Antioquia. Capparidastrum dugandii is distinguished from other species of subgen. Pulviniglans molecularly and by the lowest number of stamens (18–20). In addition, the species is endemic to the Cauca biogeographic province.